Odpowiedzi

2009-12-06T13:56:58+01:00
A) w(x)= x3 - x2 + 6x - 6
W(x) = x²(x -1) +6(x -1)
W(x) = (x-1)(x²+6)

b) w(x) = 5x3 + 10x2 + x + 2
W(x) = 5x²(x +2) +1(x +2)
W(x) = (x +2)(5x² +1)

c) w(x) = 3x3 + 6x2 + 2x + 4
W(x) = 3x²(x+2) +2(x+2)
W(x) = (x+2)(3x² +2)

d) w(x) = 2x3 - x2 + 8x - 4
W(x) = x²(2x -1) + 4(2x -1)
W(x) = (2x-1) (x² +4)
2 5 2
2009-12-06T13:57:31+01:00
A)x³-x²+6x-6=x²(x-1)+6(x-1)=(x-1)(x²+6)
b)5x³+10x²+x+2=5x²(x+2)+1(x+2)=(x+2)(5x²+1)
c)3x³+6x²+2x+4=x(3x²+2)+2(3x²+2)=(3x²+2)(x+2)
d)2x³-x²+8x-4=x²(2x-1)+4(2x-1)=(2x-1)(x²+4)